2016
DOI: 10.1016/j.ypmed.2016.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Physically active vs. sedentary academic lessons: A dose response study for elementary student time on task

Abstract: Background Physically active academic lessons are an effective intervention to reduce sedentary time and increase student physical activity. They have also been shown to enhance task engagement, as indicated by observations of attention and behavior control, Time On Task (TOT). However, it is not clear if the improved TOT stems from the physical activity or if it is the result of an enjoyable break from traditional instruction? If it is due to physical activity, what dose of intensity is required for the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(119 citation statements)
references
References 45 publications
(44 reference statements)
5
106
0
6
Order By: Relevance
“…This is good news for those seeking to implement CBPA, as it may not take more than a few minutes of CBPA in a school day to facilitate significant gains in student PA. Future research should investigate whether short bouts of CBPA can facilitate improvements in student behavior, in line with the positive behavioral outcomes shown after longer (10-15 min) moderate-to vigorousintensity classroom activities. 24 We found that males and females had similar step counts when engaging in CBPA, and CBPA was an important contributor to school-day PA for older students. These findings have important implications for school policies and practices, as they reinforce the notion that CBPA should be promoted to teachers of all grades.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…This is good news for those seeking to implement CBPA, as it may not take more than a few minutes of CBPA in a school day to facilitate significant gains in student PA. Future research should investigate whether short bouts of CBPA can facilitate improvements in student behavior, in line with the positive behavioral outcomes shown after longer (10-15 min) moderate-to vigorousintensity classroom activities. 24 We found that males and females had similar step counts when engaging in CBPA, and CBPA was an important contributor to school-day PA for older students. These findings have important implications for school policies and practices, as they reinforce the notion that CBPA should be promoted to teachers of all grades.…”
Section: Discussionmentioning
confidence: 63%
“…Data from a nationally representative sample of 640 US public elementary schools in 2013-2014 indicated that although over 70% of school administrators reported some use of CBPA at their school, the number of teachers engaged in the practice was often less than 50%. 22 However, given the growing evidence base showing that CBPA can improve student on-task behavior, 5,23,24 the integration of PA into lessons should be viewed as an effective classroom management strategy.…”
mentioning
confidence: 99%
“…Children spend a large proportion of the school day seated and it is estimated that in primary schools children are seated for 50-70% of their time in the classroom (Clemes et al, 2015). Integration of physical activity into normal academic classroom time could break up or reduce sitting and may have added academic benefits such as improved attention to task, motivation and enjoyment of learning, and attainment in certain subjects (Grieco, Jowers, Errisuriz, & Bartholomew, 2016;Martin & Murtagh, 2017;Mullender-Wijnsma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies show the benefits of PA in the classroom (Fedewa et al, 2015;Mullender-Wijnsma et al, 2015;Donnelly and Lambourne, 2011;Grieco et al, 2016;Ma et al, 2014;Mahar et al, 2006;Mahar, 2011;Finn and McInnis, 2014;Howie et al, 2014), but there is a gap in the research when it comes to evaluating the reality of PA implemented in classrooms. More research should be conducted to expand what is known about PA in the classroom and whether classrooms in other geographic locations are meeting the recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing PA during the school day was shown to improve children's achievements in mathematics and reading (Fedewa et al, 2015;Mullender-Wijnsma et al, 2015), as well as improving performance on standardized testing (Donnelly and Lambourne, 2011). Incorporating PA into the classroom setting was also shown to be beneficial to increasing the amount of time students spent focusing on the academic tasks assigned them (Mullender-Wijnsma et al, 2015;Ma et al, 2014;Mahar et al, 2006;Mahar, 2011;Grieco et al, 2016). Students have also been reported to respond positively to exercise being implemented in the classroom (Howie et al, 2014;Finn and McInnis, 2014), which helps to improve enjoyment of school and the classroom environment.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%